2011
DOI: 10.1007/s00027-011-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological and ecological mechanisms for overcoming sperm limitation in invasive dreissenid mussels

Abstract: Many broadcast-spawning benthic invertebrates are subject to sperm limitation yet achieve high population densities, as for example dreissenid mussels (Dreissena polymorpha and Dreisssena bugensis) that were introduced into the Laurentian Great Lakes. The question remains whether biological or ecological/physical mechanisms reduce sperm limitation. Gamete dilution/longevity experiments were undertaken to determine whether dreissenid mussels are subject to sperm limitation, and computational fluid dynamic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…This was the case for both D. polymorpha and D. bugensis in the laboratory and for D. bugensis in the field, and thus we conclude that these dreissenid species are sperm limited. These results are also consistent with computational fluid dynamic models of sperm dilution and transport, which predicted an increase in dilution with distance under the influence of mussel roughness (Quinn and Ackerman 2011). D. polymorpha and D. bugensis are the first freshwater broadcast spawners that have been demonstrated to be sperm limited.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This was the case for both D. polymorpha and D. bugensis in the laboratory and for D. bugensis in the field, and thus we conclude that these dreissenid species are sperm limited. These results are also consistent with computational fluid dynamic models of sperm dilution and transport, which predicted an increase in dilution with distance under the influence of mussel roughness (Quinn and Ackerman 2011). D. polymorpha and D. bugensis are the first freshwater broadcast spawners that have been demonstrated to be sperm limited.…”
Section: Discussionsupporting
confidence: 88%
“…Bottom roughness influenced the fluid dynamic environment of the near‐bed region, which has been predicted to affect fertilization success as well as larval settlement (Crimaldi et al 2002; Quinn and Ackerman 2011). In this study, it was the abrupt change in bottom roughness (e.g., space between mussel patches) that led to downstream recirculation, which enhanced fertilization success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that an alternate choice of λ and k could have resulted in different λ/k ratios leading to isolated-roughness and wake-interference flows, where settlement would likely increase. Quinn and Ackerman (2011, 2012, 2014, found that mussel shells placed uniformly at high density on the bottom of a flow chamber led to skimming flow, in contrast to wake-interference flow observed under a low mussel-density configuration.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, this is the first study to examine scalar transport in the near-bed region as it is influenced by bottom roughness of differing geometries and λ/k ratios. This comparison, which is pertinent to benthic organisms in general, builds on results from models of sperm transport over roughness elements of different roughness height, k (Quinn and Ackerman, 2012). In that case, the results indicate that above a certain k, scalar (sperm) released within the space between two roughness elements was retained within the space rather than being transported downstream.…”
Section: Discussionmentioning
confidence: 95%